Asymmetric Organocatalytic Double-Conjugate Addition of Malononitrile to Dienones: Efficient Synthesis of Optically Active Cyclohexanones - Li, Xue-ming; Wang, Bo; Zhang, Jun-min; Yan, Ming (Organic letters, 2011)
9-Amino-9-deoxyepiquinine efficiently catalyzed the double-conjugate addition of malononitrile to dienones. A number of 1,1,2,6-tetrasubstituted cyclohexanones were prepared in good yields, diastereoselectivities, and excellent enantioselectivities.